Genetic algorithm based optimization of overcurrent relay coordination for improved protection of DFIG operated wind farms - Rezaei N.; Nasir Uddin M.; Khairul Amin I.; Lutfi Othman M.; Marsadek M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Asynchronous generators; Electric relays; Electric utilities; Genetic algorithms; IEEE Standards; Overcurrent protection; Wind power; Intelligent Algorithms; Nonlinear characteristics; Novel genetic algorithm; Overcurrent relay coordination; Overcurrent relays; Power system protection; Relay coordination; Wind farm; Electric power system protection